Acetylation of cell wall is required for structural integrity of the leaf surface and exerts a global impact on plant stress responses - Nafisi, Majse; Stranne, Maria; Fimognari, Lorenzo; Atwell, Susanna; Martens, Helle J.; Pedas, Pai R.; Hansen, Sara F.; Nawrath, Christiane; Scheller, Henrik V.; Kliebenstein, Daniel J.; Sakuragi, Yumiko (Frontiers in Plant Science, 2015)
The epidermis on leaves protects plants from pathogen invasion and provides a waterproof barrier. It consists of a layer of cells that is surrounded by thick cell walls, which are partially impregnated by highly hydrophobic cuticular components. We show that the Arabidopsis T-DNA insertion mutants of REDUCED WALL ACETYLATION 2 (rwa2), previously identified as having reduced O-acetylation of both pectins and hemicelluloses, exhibit pleiotrophic phenotype on the leaf surface. The cuticle layer appeared diffused and was significantly thicker and underneath cell wall layer was interspersed with electron-dense deposits. A large number of trichomes were collapsed and surface permeability of the leaves was enhanced in rwa2 as compared to the wild type. A massive reprogramming of the transcriptome was observed in rwa2 as compared to the wild type, including a coordinated up-regulation of genes involved in responses to abiotic stress, particularly detoxification of reactive oxygen species, and defense against microbial pathogens (e.g. lipid transfer proteins, peroxidases). In accordance, peroxidase activities were found to be elevated in rwa2 as compared to the wild type. These results indicate that cell wall acetylation is essential for maintaining the structural integrity of leaf epidermis, and that reduction of cell wall acetylation leads to global stress responses in Arabidopsis.